Immunomodulatory potential of exopolysaccharides from Lactiplantibacillus plantarum YY-112 - Mengfan Luo; Wanyi Zhou; Wenyang Tao; Jianrong Xing; Jingrui Li; Yuxing Guo; Ying Yang (Food Science and Human Wellness)
In vitro simulated colonic fermentation studies have shown the prebiotic potential of exopolysaccharides from Lactiplantibacillus plantarum YY-112 (YEPS). Its immunomodulatory effects and related mechanisms were systematically investigated in this study. We observed that YEPS intervene in immune responses and improve intestinal microbial structure in normal mice, including significantly increasing the relative abundance of Enterorhabdus and norank_f_norank_o_Clostridia UCG-014 as well as decreasing that of unclassified_c_Bacilli (P < 0.05). In the immunocompromised mouse model, YEPS decreased interleukin-6 levels (P < 0.05) and protected the spleen by regulating lymphocyte levels. YEPS preserved the intestinal barrier by improving Mucin 2, Zonula occludens protein 1, and Occludin expression. Moreover, YEPS significantly reduced the relative abundance of Bacillus, unclassified_c_Bacilli, Lachnoclostridium, Eubacterium_xylanophilum_group, and Desulfovibrio (P < 0.05), potentially enhancing mice immunity by improving the intestinal microbiota associated with immune function. In conclusion, YEPS can be used as a natural functional extract with prebiotic effects that may improve host immunity. This provided the basis for the application of YEPS as a novel potential food additive.